Insulin-like growth factor I enhances the formation of type I collagen in hydrocortisone-treated human osteoblasts. Issue 5 (October 1993) - Jonsson, Kenneth B.; Ljunghall, Sverker; Karlström, Olle; Johansson, Anna G.; Mallmin, Hans; Ljunggren, Östen
Abstract : We have studied the effect of insulin-like growth factor I (IGF-I) on the formation of osteocalcin and type I collagen in isolated human osteoblasts. IGF-I at and above 0.1 nM stimulated the formation of type I collagen as measured by the type I procollagen carboxyterminal peptide (PICP), in human osteoblasts, incubated for 72 hrs in serumfree conditions. The secretion of osteocalcin was not affected by IGF-I while 1, 25(OH)2 vitamin D3 significantly enhanced the formation of osteocalcin. When human osteoblast-like cells were incubated with hydrocortisone (1 μM), a significant decrease in the release of both PICP and osteocalcin was seen. Addition of IGF-I to human osteoblasts also treated with hydrocortisone normalized the PICP-formation but did not affect the suppressed osteocalcin-formation. These data indicate that IGF-I reverses selective effects of hydrocortisone on bone.